Non conventional technologies in lipid modifications - Phuah, Eng-Tong; Lee, Yee-Ying; Tang, Teck-Kim; Akoh, Casimir; Cheong, Ling-Zhi; Tan, Chin-Ping; Wang, Yong; Lai, Oi-Ming (Annual Reviews, 2024)
Lipid modifications play a crucial role in various fields, including food science, pharmaceuticals, and biofuel production. Traditional methods for lipid modifications involve physical and chemical approaches or enzymatic reactions, which often have limitations in terms of specificity, efficiency, and environmental impact. In recent years, nonconventional technologies have emerged as promising alternatives for lipid modifications. This review provides a comprehensive overview of nonconventional technologies for lipid modifications, including high-pressure processing, pulsed electric fields, ultrasound, ozonation, and cold plasma technology. The principles,mechanisms, and advantages of these technologies are discussed, along with their applications in lipid modification processes. Additionally, the challenges and future perspectives of nonconventional technologies in lipid modifications are addressed, highlighting the potential and challenges for further advancements in this field. The integration of nonconventional technologies with traditional methods has the potential to revolutionize lipid modifications, enabling the development of novel lipid-based products with enhanced functional properties and improved sustainability profiles.